Innovative approaches to individual and community resilience : from theory to practice - Nemeth, Darlyne Gaynor; Olivier, Traci W. (Academic Press, 2017)
Resilience is a biopsychosocial phenomenon-it encompasses personal, interpersonal, and community experiences.iAInnovative Approaches to Individual and Community Resilience reviews the current research and details differing levels and approaches to resilience. On a microlevel, this book specifies how to develop appropriate coping strategies, maintain cognitive flexibility, and identify, label, and share feelings before acting upon them. On a macrolevel, it defines and explores environmental resilience, social resilience, community resilience, and family resilience.iA It focuses on the importance ofiAfamily, community, and spiritual bonds, in order to share experiences and enhance posttraumatic healing.iA The need to be firmly grounded in today, while learning from yesterday, in order to cope with the requirements of tomorrow is the primary emphasis of thisiAbook.iAiA.